Discovery of the genus Paraleuctra (Plecoptera: Leuctridae) from Palearctic China, with description of P. qilianshana sp. nov. - Kong, Fanbin; Yang, Ding; Li, Weihai (Zootaxa, 2013)
A new species of the genus Paraleuctra, P. qilianshana sp. nov., is described from Mt. Qilianshan, Gansu Province, China. The new species is the first representative of Paraleuctra discovered in the Palearctic Region of China. The new species is compared with its regional congeners.